Empirical Evidence on Status of Street Vendors in Nepal amid COVID-19: A Structural Equation Modeling Approach - Bista, Sushmita; Adhikari, Dipak Bahadur; Dhakal, Krishna (Quest Journal of Management and Social Sciences, 2024)
Background: During the COVID-19 pandemic, street vending businesses faced severe disruptions, exacerbating poverty and livelihood challenges for vendors. The government's neglect of this sector has further intensified these issues, highlighting the need for a comprehensive analysis of the situation. Objectives: This study aims to investigate the impact of COVID-19 on street vendors in Kathmandu Valley. Specifically, it explores the relationships between poverty, unemployment, and street vending, and examines the role of migration as a mediating factor. Methods: An explanatory research design was employed, utilizing a non-probability convenience sampling technique to collect data from 202 street vendors. Data were gathered using KOBO Toolbox and a structured questionnaire. Both descriptive and inferential statistics were applied, with Structural Equation Modeling (SEM) used to analyze relationships and impacts. Results: The analysis reveals a significant impact of poverty on unemployment among street vendors during the pandemic. Migration has a notable influence on street vending and unemployment, serving as a mediator between poverty and street vending activities. Domestic migration, in particular, has been pivotal in enhancing street vending in Kathmandu Valley. Conclusion: The study underscores the need for regulatory authorities at central, provincial, and local levels to develop a legal and political framework to support street vendors. Implementing such measures could significantly improve their status and mitigate the adverse effects of the pandemic on their livelihoods. Paper Types: Research Paper Keywords: Poverty, Migration, Street vending, Informal sector, Structural Equation Modelling, Nepal JEL Classification: E26, O17